Collaborative Workspaces to Accelerate Discovery. (9th May 2017) - Meade, Bernard; Fluke, Christopher; Cooke, Jeff; Andreoni, Igor; Pritchard, Tyler; Curtin, Christopher; Bernard, Stephanie R.; Asher, Albany; Mack, Katherine J.; Murphy, Michael T.; Vohl, Dany; Codoreanu, Alex; et al.
Abstract: By applying a display ecology to the Deeper, Wider, Faster proactive, simultaneous telescope observing campaign, we have shown a dramatic reduction in the time taken to inspect DECam CCD images for potential transient candidates and to produce time-critical triggers to standby telescopes. We also show how facilitating rapid corroboration of potential candidates and the exclusion of non-candidates improves the accuracy of detection; and establish that a practical and enjoyable workspace can improve the experience of an otherwise taxing task for astronomers. We provide a critical road test of two advanced displays in a research context—a rare opportunity to demonstrate how they can be used rather than simply discuss how they might be used to accelerate discovery.